Acute effect of self-myofascial release using rolling bar on lower limb flexibility among adolescents / Muhammad Aizuddin Ismail - Ismail, Muhammad Aizuddin (Faculty of Sports Science And Recreation, 2019)
The purpose of this study is to investigate the acute effect of self-myofascial release (SMR) using rolling bar on lower limb flexibility among adolescents. A total of twenty- four subjects (N=24) from Sekolah Sukan Seberang Temerloh, Pahang were selected through purposive sampling. The study compared the result of pre-test and post-test of sit and reach test before and after applying the treatment of self-myofascial release using rolling bar. All of the subjects will perform two trials for each test. They will perform sit and reach test for the pre-test and directly apply the treatment of self-myofascial release using rolling bar, and then immediately do the post-test for sit and reach test. Sit and reach box is the instrument used to measure the distance of hand reach. This study used Paired Sample T-test for the data analysis. There is a significant effect of the hypothesis testing for the sit and reach between pre-test and post-test which is M = 2.2500, SD = .3040). To conclude, this finding suggests self-myofascial release using rolling bar produce significant acute effect on lower limb flexibility.